The Impact of Animated Cartoons on Enhancing Vocabulary Acquisition and Listening Comprehension Skill The Case of Second Year Al Zahra Middle School, Laghouat - Bedj,Soumia; Nouioua,Amira Hiba (University of Ammar Theledji -Laghouat, 2020)
In Algeria, an Arabic speaking country where English is taught as a foreign language, middle school learners and their teachers confront a variety of difficulties related to EFL learner’s lack oral performance. This research aims to investigate the impact and the effectiveness of using animated cartoons program in learning English vocabulary among 2nd year middle school and how these programs facilitate the acquisition of new vocabularies through watching them. In this study and through teaching and learning processes, the motivation derived from visual aids of cartoons has been explored as a means to ameliorate the teaching and learning of English as Foreign Language in the Algerian context. To reach such an aim, we administer a questionnaire of number of statements to students of 2nd year middle school classes. The results reveal that animated cartoons constitute positive impacts on EFL beginners’ listening, speaking, reading and writing abilities, it also develops their oral production; this indeed creates and motivates the learners and draws a less-stressful classroom atmosphere